(untitled) (Élisée - Revista de Geografia da UEG, 2021)
The research questions the socioeconomic effects of the Brazilian State’s tax exemption policy oriented to agriculture and agribusiness on the agrarian issue. The article starts from the qualitative analysis method of political economy and the reference of fiscal sociology. Aims to describe the current budget of tax subsidies of the Union and reveals how it favors agribusiness; to understand the consolidation of this policy in the country, especially in the 1960/1970s, and after the 2000s; and to report the socioeconomic implications of this state intervention on agrarian relations, using the concepts of critical geographer David Harvey as the guiding thread of the analysis. It was identified that the action of the Brazilian State, by instituting tax benefits, favored the interests of productive and financial capital. It was concluded that this policy generates imbalances in land relations, changing land income, increasing financial market control over political decisions.